Public Health Nutrition (Italian Journal of Public Health, 2008)
Abraham Maslow (1908 – 1970) has set up a hierarchy of five levels of basic needs. Of those that are considered to be basic physiological needs hunger, thirst as well as bodily comforts are considered to be the most important. Physiological needs are the strongest needs because if a person were deprived on all needs it is these physiological needs that would take the highest priority. As food is characterized as a basic need, we should have a special view on our daily food and our handling of it. Most people do not act careful with their daily intake of food. In the last decades, the increases of nutrition-associated diseases such as overweight and obesity and on the other hand underweight have been recorded. From a life-span approach, the problem has its offset point in the early age of development, namely in children and adolescents. Malnutrition, overweight and obesity limit children’s personal quality of life in terms of unhappiness with their own body, opposition or even rejection in peer group communication and general difficulties in day-to-day social interaction. A close connection between physical stature and the development of a negative self-concept and a low self-esteem is postulated.